On the stability of bessel differential equation - Jung, Soon-Mo (2022)
Using power series method, Kim and Jung (2007) investigated the Hyers-Ulam stability of the Bessel differential equation, x^2y′′(x)+xy′(x)+(x^2−α^2)y(x) = 0, of order non-integral number α > 0. Also Bicer and Tunc (2017) obtained new sufficient conditions guaranteeing the Hyers-Ulam stability of Bessel differential equation of order zero. In this paper, by classical integral method we will investigate the stability of Bessel differential equations of a more generalized order than previous papers. Also, we will consider a more generalized domain (0, a) for any positive real number a while Kim and Jung (2007) restricted the domain near zero.